Produce More Energy: How, When and How - Vargas, Leiner (2009)
To increase electricity generation is not the only available solution for an electricity system. Many different ways and technologies are available as well as different institutions to support them; the main problem is to define the right institutional setting in order to achieved sustainable path of sector development. The paper tried the issue of electricity sector sustainability with respect to the an-swers to the questions: how?, when? and how much? Electricity must be generated from different sources under a market oriented electricity institutional background.